2017
DOI: 10.1016/j.rbmo.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Multi-centre assessment of nitroblue tetrazolium reactivity in human semen as a potential marker of oxidative stress

Abstract: The nitroblue tetrazolium (NBT) reaction as a tracer of oxidative stress was examined in 707 ejaculates from seven clinics. Semen was initially surveyed by classifying the NBT reaction using a pre-established rank for the Oxisperm® test based on three colourimetric levels: L1, low (n = 141 [20%]); L2, medium (n = 538 [76%]) and L3, high (n = 28 [4%]). L3 was indicative of a high level of superoxide anions. Halosperm® chromatin dispersion assay was used to analyse samples of ejaculates 30 min after ejaculation;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Those who were first suspected of having G6PD by NBS were further examined by a NBT G6PD/6PGD test (Gosálvez et al, ). The assays were performed according to the manufacturers’ protocols (YZB/0039–2014; Zhongshan Bio‐tech, China and YZB/0829–2011; Micky Med, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who were first suspected of having G6PD by NBS were further examined by a NBT G6PD/6PGD test (Gosálvez et al, ). The assays were performed according to the manufacturers’ protocols (YZB/0039–2014; Zhongshan Bio‐tech, China and YZB/0829–2011; Micky Med, China).…”
Section: Methodsmentioning
confidence: 99%
“…Later, it was expanded to other regions of China for its clinical significance in the identification of neonatal jaundice and acute or chronic hemolysis (Kaplan et al, ; Moiz, Nasir, Khan, Kherani, & Qadir, ). In China, the routine assays for G6PD NBS screening are based on the semiquantitative G6PD activity fluorescence test first (Howson et al, ), and then confirmed by nitroblue tetrazolium (NBT) G6PD/6PGD test (Gosálvez et al, ). The semiquantitative G6PD activity test can accurately identify hemizygous males and homozygous females.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the main concern is that several tissue reductases, including sperm cytochromes (CP450R and Cb5R) [101,102], can reduce both probes and, therefore, lead to artefactual NAD(P)H-dependent reduction and the generation of O 2 • − by autoxidation [117,118] (Figures 2 and 3). However, despite these consistent factors, many studies have used this approach to indirectly report the presence of O 2 • − in sperm and further correlate it with semen quality [119][120][121], capacitation [122], hyperactivation [123], DNA integrity [120,124,125], apoptosis [120], IVF outcomes [121], among others. Yet, caution and a deep understanding of the limitations of both detection methods must guide the interpretation of these data.…”
Section: Lucigenin and Tetrazolium Saltsmentioning
confidence: 99%
“…Previous studies in spermatozoa reported application of this salt to measure seminal ROS production as an oxidative stress tracer [Amarasekara et al, 2014;Gos alvez et al, 2017] related to impaired sperm function (mobility and DNA integrity) [Tunc et al, 2010], as well as to evaluate mitochondrial morphology and functionality [Gaczarzewicz et al, 2003;Piasecka et al, 2004;Mukhopadhyay et al, 2008].…”
Section: Introductionmentioning
confidence: 99%